Synaptophysin regulates the kinetics of synaptic vesicle endocytosis in central neurons - Kwon, Sung E. (2011)
Despite being the most abundant synaptic vesicle membrane protein, the function of synaptophysin remains enigmatic. For example, synaptic transmission was reported to be completely normal in synaptophysin knockout mice; however, direct experiments to monitor the synaptic vesicle cycle have not been carried out. Here, using optical imaging and electrophysiological experiments, we demonstrate that synaptophysin is required for kinetically efficient endocytosis of synaptic vesicles in cultured hippocampal neurons. Truncation analysis revealed that distinct structural elements of synaptophysin differentially regulate vesicle retrieval during and after stimulation. Thus, synaptophysin regulates at least two phases of endocytosis to ensure vesicle availability during and after sustained neuronal activity.